Characteristics of iron powder ASC100.29 mixed with aluminium (AL) powder formed at room temperature and above room temperature - Sasikumar A/L Suriya Sandran (2023)
This thesis mainly presents the investigation of the characteristics of iron powder ASC 100.29 mixed with aluminium (A1) powder formed at room temperature and above room temperature. The iron powder ASC 100.29 was mixed with different weightage of aluminium powder which is 0%, 5%, 10% and 15% compacted i.e. temperature 30C, 60C, and 90C respectively. Once the compaction process was done, the product of the compaction process is called green sample. There were total 12 green samples generated during the compaction process.